Teaching scientific inquiry skills : a handbook for bioscience educators in Australian universities. - Elliott, Kristine; Boin, Anna; Irving, Helen; Johnson, Elizabeth; Galea, Victor (Australian Learning and Teaching Council, 2010)
This project examined current teaching practice in bioscience disciplines in Australian universities. Twenty-six cases were identified where the priority to teach scientific inquiry skills to students had influenced the design of the approach. Cases were identified from nine universities, across eleven bioscience disciplines and were developed for undergraduate teaching. Cases have been described using a framework based on the degree of inquiry inherent in student tasks, the degree of independence expected of students in performing tasks, the learning objectives students were expected to achieve, and the learning environment in which tasks were carried out. Generally, technology played three broad roles in supporting the development of scientific inquiry skills: Guidance for learning, communication amongst student peers, and between students and educators, and as authentic tools of the profession. Learning designs have been created of six cases, which were innovative, made use of educational technologies, and represented a diversity of practice. Recommendations have been made about the ways educators might evaluate student learning of scientific inquiry skills. Key findings of the project are published in a handbook Teaching scientific inquiry skills, written for bioscience educators with practical ideas for adopting improved teaching practice that explicitly targets scientific inquiry skills as learning outcomes.